The future of the Malaysian beef industry - Mohd Hafiz Jamaludin; Hassan, M.H; Md. Ruhul Amin; Zulhisyam Abdul Kari @ Abdullah (Universiti Malaysia Kelantan, 2014)
Beef is an important protein food source, and an important commodity for a country like Malaysia. Countries such as South Korea and Japan have not only been able to increase beef output, but have also introduced their breed, the Hanwoo and Wagyu cattle respectively into the international beef industry. Meanwhile for Malaysia, it was expected that local production can only fulfill 30% of the country’s total beef demand for 2012. Although research in enhancing cattle production started concurrently with countries such as South Korea, the 40 years of research put into enhancing the local production of cattle species for their beef has been futile. Drastic measures need to be taken to ensure the country’s self-sufficiency in the cattle industry, and identifying the causes leading to the declination should be the main priority to prevent further deterioration of the industry.